VHL Genetic Alteration in CCRCC Does Not Determine De-Regulation of HIF, CAIX, hnRNP A2/B1 and Osteopontin - Michelle J. Nyhan; Shereen M. El Mashad; Tracey R. O’Donovan; Sarfraz Ahmad; Chris Collins; Paul Sweeney; Eamonn Rogers; Gerald C. O’Sullivan; Sharon L. McKenna (Analytical Cellular Pathology)
Background: von Hippel–Lindau (VHL) tumour suppressor gene inactivation is associated with clear cell renal cell carcinoma (CCRCC) development. The VHL protein (pVHL) has been proposed to regulate the expression of several proteins including Hypoxia Inducible Factor-α (HIF-α), carbonic anhydrase (CA)IX, heterogeneous nuclear ribonucleoprotein (hnRNP) A2/B1 and osteopontin. pVHL has been characterized in vitro, however, clinical studies are limited. We evaluated the impact of VHL genetic alterations on the expression of several pVHL protein targets in paired normal and tumor tissue.